Uji Aktivitas Antibakteri Ekstrak Fermentasi Bawang putih tunggal (Allium sativum L.) Terhadap Bakteri Staphylococcus aureus dan Methicillin-resistant Staphylococcus aureus (MRSA) - Sapitri, Alfi; Marbun, Eva Diansari; Arisetya, Dian (Herbal Medicine Journal, 2025)
The pathogenicity of S. aureus bacteria is often associated with purulent wound infections in both humans and animals, which is the main cause of pyemia cases. Methicillin-Resistant Staphylococcus aureus (MRSA) is a Staphylococcus aureus bacteria that is resistant or immune to methicillin-type antibiotics and its derivatives. This study aims to see the activity of extracts from single garlic fermentation (Allium sativum L) which have antibacterial effects against Staphylococcus aureus and Methicillin-Resistant Staphylococcus aureus (MRSA) bacteria. This study was conducted at the Pharmacy Laboratory of Sari Mutiara Indonesia University in June-August 2024. This research method was carried out experimentally, the extraction was maceration and the media was tested using MHA to see the bacterial inhibition power. Based on the results of phytochemical screening examinations of single garlic fermentation extracts, it showed the presence of chemical compound groups in the form of Alkaloids, Flavonoids, Tannins, and Saponins. Where the concentration of single garlic fermentation extract is 5%; 10%; 15%. The results of the inhibition test against Staphylococcus aureus bacteria were 9.74 mm; 11.48 mm; 12.19 mm, positive control (chloramphenicol) 12.35 mm. The results of the inhibition test against Methicillin-Resistant Staphylococcus aureus (MRSA) bacteria were 8.49 mm; 10.58 mm, 11.33 mm, positive control (chloramphenicol) 11.42 mm. Ethanol extract from single garlic fermentation has weak antibacterial activity against Staphylococcus aureus and Methicillin-Resistant Staphylococcus aureus (MRSA) bacteria.